Pengaruh Konten Materi Dakwah Terhadap Tingkat Ketertarikan Viewers Pada Podcast Log In Channel YouTube Deddy Corbuzier - Rokhimah, Annisa Nur; Effendi, Arif (Hikmah, 2024)
This research wish to know the content of Dakwah material on the Podcast Log In to Deddy Corbuzier's YouTube channel ; the level of interest of viewers in Podcast Log In to Deddy Corbuzier's YouTube channel ; the influence of Dakwah material content on the level of interest of viewers in Podcast Log In to Deddy Corbuzier's YouTube Channel. This research is a type of correlational quantitative research that correlates two variables. The subject of this research is the Interest of Viewers in the Log In Podcast on Deddy Corbuzier's YouTube Channel. Specifically, the viewers of the Log In podcast on Deddy Corbuzier's YouTube channel, with the entire population of viewers of the Log In podcast on Deddy Corbuzier's YouTube channel, with 80 respondents as the sample. The data analysis technique to test the hypothesis in this study is to use the Product Moment correlation analysis technique. The results showed that the content of Dakwah material on the Podcast Log In to Deddy Corbuzier's YouTube channel was in sufficient catagory; how the level of interest of viewers in Podcast Log In to Deddy Corbuzier's YouTube was in sufficient category; the results of correlation  are r xy = 0,603 or the category was into the strong correlation category.